Kinetic analysis of retention of SO2 using waste ulexite ore in an aqueous medium - Karagoz, Ozlem; Çopur, Mehmet; Kocakerim, M. Muhtar (Elsevier Science Bv, 2018)
This study was carried out under atmospheric pressure and examined the kinetics of retention of SO2, a toxic gas, by waste ulexite ore (WUO) from a boron concentration plant, as well as the kinetics of passing B2O3 content of WUO to solution. The parameters of temperature, solid-to-liquid ratio, particle size, gas flow rate, and stirring speed were selected for the experiments carried out in a jacketted cylindirical glass reactor. The data on retention-dissolution and an XRD graph showed that SO2 had been captured as CaSO3 center dot 0.5H(2)O, and that the B2O3 content of WUO had almost completely passed into the aqueous medium. A kinetic evaluation, performed with the retention-dissolution data using kinetic models for heterogenous reactions, found that the kinetics model for SO2 retention fitted diffusion through product layer control. In addition, the kinetics model for the B2O3 dissolution fitted the diffusion through product film control. Activation energies for SO2 retention in solid waste and B2O3 dissolution were 6196 J mol(-1) and 15436 J mol(-1) respectively.
Keywords: Retention; Ulexite waste; Dissolution; Kinetics